2013
DOI: 10.1002/wrcr.20185
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of hyporheic exchange and biogeochemical cycling around cross‐vane restoration structures: Implications for stream restoration design

Abstract: [1] Natural channel design restoration projects in streams often include the construction of cross-vanes, which are stone, dam-like structures that span the active channel. Vertical hyporheic exchange flux (HEF) and redox-sensitive solutes were measured in the streambed around four cross-vanes with different morphologies. Observed patterns of HEF and redox conditions are not dominated by a single, downstream-directed hyporheic flow cell beneath cross-vanes. Instead, spatial patterns of moderate (<0.4 m d À1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 67 publications
4
99
0
Order By: Relevance
“…In this study, we assumed the Field of Dreams hypothesis (Sudduth et al, 2011) (that if desirable habitat is available, organisms will occupy the space) holds true, which is not always the case for restoration projects. However, there have been many examples of the positive effects that restoration projects have on nutrient cycling, specifically in the hyporheic zone (Gordon et al, 2013;Hester et al, 2009). We found that the size of the hyporheic zone (A HTS ), where we assumed denitrification was occurring exclusively, was the single most sensitive model parameter that can significantly be affected by restoration projects to the amount of N removed.…”
Section: Implications For the Management Of Streamsmentioning
confidence: 82%
See 1 more Smart Citation
“…In this study, we assumed the Field of Dreams hypothesis (Sudduth et al, 2011) (that if desirable habitat is available, organisms will occupy the space) holds true, which is not always the case for restoration projects. However, there have been many examples of the positive effects that restoration projects have on nutrient cycling, specifically in the hyporheic zone (Gordon et al, 2013;Hester et al, 2009). We found that the size of the hyporheic zone (A HTS ), where we assumed denitrification was occurring exclusively, was the single most sensitive model parameter that can significantly be affected by restoration projects to the amount of N removed.…”
Section: Implications For the Management Of Streamsmentioning
confidence: 82%
“…Common restoration structures include surface structures such as baffles (Ensign and Doyle, 2005), boulders, cross-vanes, J-hooks, rock weirs, and oxbow ponds which slow water movement, increasing residence time and the opportunity of the water column to interact with stream sediment and biota (Gordon et al, 2013;Kasahara and Hill, 2006;Passeport et al, 2013Radspinner et al, 2010. However, some of these structures can lose effectiveness over time due to clogging of hyporheic flow paths by debris Hill, 2006, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We simulated two in-stream structures (weirs) in the 90 m reach that represent common in-stream restoration structures such as boulder weirs, log dams, w-weirs, upstream v's, and cross vanes (Doll et al, 2003;Roni et al, 2006;NRCS, 2007;Hester and Doyle, 2008;Lautz and Fanelli, 2008;Gordon et al, 2013). Each structure was 1 m long (thick) in the direction of flow, 3 m long perpendicular to the flow, and each extended 0.3 m above the streambed and approximately 0.2 m (one computational layer) into the streambed (Azinheira et al, 2014).…”
Section: Hydraulic Parameters and Boundary Conditionsmentioning
confidence: 99%
“…Interaction between surface water and groundwater often occurs in the hyporheic zone (HZ) and has important implications on a variety of water issues including solute and contaminant transport, ecological diversity, stream restoration design and nutrient dynamics (Gordon et al 2013). Crispell and Endreny (2009) further indicate that hyporheic exchange that arises from this interaction has significant impacts on biogeochemical, microbial and ecological processes that occur in the streams, and even in the aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Conant (2004), first, proposed high-density flux measurements combined with streambed temperature and mini-piezometers data as forming the basic conceptual framework of interaction between surface water and groundwater. Additionally, several studies have investigated HEF near beaver dams, cross-vane restoration structures and other local morphology (Lautz et al 2006;Rosenberry and Pitlick 2009;Käser et al 2009;Briggs et al 2012;Sawyer et al 2012;Gordon et al 2013;Karan et al 2014); however, not much has been reported on the spatial and temporal variations of HEF estimated along an entire across-river transect at multiple-depths and multiple locations. Applying the Darcy equation, Gerecht et al (2011) assessed the hydrologic impacts of HEF by simultaneous temperature and head monitoring across a bed-to-bank transect, although it was not a complete river transect.…”
Section: Introductionmentioning
confidence: 99%